Forced Dependency and Legal Barriers: Implications of the UK’s Immigration and Social Security Policies for Minoritized Women Living in Abusive Intimate Relationships in Northern Ireland - McWilliams, Monica (Oñati Socio-Legal Series, 2015)
This paper examines the complexities of the help-seeking process of minoritized women (primarily asylum-seekers and immigrants) experiencing domestic violence in Northern Ireland. The term ‘minoritized’ is used here to emphasize that "minority" status is not a static or innate trait of certain groups but instead is the outcome of a process of being positioned as a minority. The paper addresses the intersections of ethnicity, nationality, class and gender and shows how state policies in relation to immigration and social security reinforce inequalities in gendered power relations. Despite attempts to improve the social security and immigration systems, the findings from a Northern Ireland study show how recent policy changes have not addressed the systemic institutional racism and institutionalised patriarchy in these agencies. Where avenues for action are undermined by such practices, the policies raise concerns about the safety and protection of minoritized women living in abusive relationships. We argue that the UK is failing to meet its human rights responsibilities to provide adequate support and assistance to minoritized women in abusive relationships and conclude that delivering state accountability alongside a human rights framework based on security, autonomy, liberty and equality is what is needed.